Effectiveness of mechanical thinning and prescribed burning on fire behavior in Pinus nigra forests in NE Spain - Piqué, Míriam; Domènech, Rut (The Science of the total environment, 2018)
Fuel treatments can mitigate present and future impacts of climate change by reducing fire intensity and severity. In recent years, Pinus nigra forests in the Mediterranean basin have been dramatically affected by the new risk of highly intense and extreme fires and its distribution area has been reduced. New tools are necessary for assessing the management of these forests so they can adapt to the challenges to come. Our main goal was to evaluate the effects of different fuel treatments on Mediterranean Pinus nigra forests. We assessed the forest response, in terms of forest structure and fire behavior, to different intensities of low thinning treatments followed by different slash prescriptions (resulting in: light thinning and lop and scatter; light thinning and burn; heavy thinning and lop and scatter; heavy thinning and burn; and, untreated control). Treatments that used fire to decrease the resulting slash were the most effective for reducing active crown fires decreasing the rate of spread and flame length more than 89%. Low thinning had an effect on torching potential, but there was no difference between intensities of thinning. Only an outcoming crown fire could spread actively if it was sustained by a high-enough constant wind speed and enough surface fuel load. Overall, treatments reduce fire intensity and treated areas have a more homogenous fire behavior response than untreated areas. This provides opportunities to extinguish the fire and reduce the probability of trees dying from the fire. It would be helpful to include ecological principles and fire behavior criteria in silvicultural treatment guidelines in order to perform more efficient management techniques in the future. [Display omitted] •The influence of thinning intensity and the type of slash management on forest fire behavior•All treatments studied reduce fire intensity and increase the resistance of Pinus nigra forests•Thinning followed by fire is the most effective treatment for reducing crown fire potential•Crown fire potential is higher for light thinning, but only with very extreme climatic conditions•Treatments provide better fire suppression opportunities and higher probabilities of tree survival